PENGARUH PUBLISITAS KASUS MENU TULIS TANGAN GARUDA INDONESIA TERHADAP CITRA GARUDA INDONESIA - Anggia Desri Pratiwi; Dewi Rachmawati (Jurnal Ranah Komunikasi, 2021)
Garuda Indonesia was in the public spotlight due to the youtube upload by one of its flight passengers on the Sydney-Denpasar-Jakarta route named Rius Vernandes regarding a list of handwritten menus distributed by cabin crew on a piece of paper thereby tarnishing the image of Garuda Indonesia which is known to be the best fullservice airline in his circle. This study aims to examine whether there is an influence from the case on the image of the airline. The research method is a quantitative approach with survey methods and data collection through research instruments in the form of questionnaires distributed directly face to face to 100 respondents. Based on the results of this study, the publicity of the Garuda Indonesia handwritten menu case significantly affects the company's image by 0.000 < 0,05. While, the magnitude of the influence of the publicity of the Garuda Indonesia handwritten menu case on the company's image is 0.540. The results showed that there was a medium influence on the quantity of publicity in the handwritten menu cases that had a publicity impact, in which the opinion of Garuda Indonesia passengers was formed so that it indirectly affected the image of Garuda Indonesia.